The Power of Respecting Others: Reconceptualization of Sociocultural Background and Students’ Learning Styles in English Classroom - Sholihah, Lilis; Sinaga, Risma Margaretha; Adha, Muhammad Mona (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The students in the class sometimes cannot define the term of cultural background among students, they did not know their learning styles, and method that can lead into effective learning. Through a deep understanding of the concept of multicultural education and a reconceptualization of the classroom as a cultural entity, we can observe how social interactions, identities, and daily life practices within it make valuable contributions to inclusive and meaningful learning. This research tried to focus on the understanding of the learners in their cultural awareness in order to have respect of others who have variety in sociocultural background and their identity. To respect on others, they have to know themselves so that they can appreciate another culture or everyone without considering their races and gender. The subject of the study was 23 students of English department of university of Lampung who come from different background and ethnicity. The method was descriptive qualitative by giving open ended questionnaire in gathering the data. The data analysis uses coding in order to get meaningful and clear description. The result shows that the students who come from different background in terms of gender, ages and ethnicity, also have variety in their learning styles. The students think that differences in sociocultural background are not big problems for them. There are ways to overcome problems that might be happened in sociocultural differences among students; for example, understand and respect each other, do not harm or make fun of others, it is also influenced by the attitude of the members which more tolerance and open minded. Their opinions on the way to achieve gender equality in the classroom is through active student participation, not discriminating, students have the same duties and obligations, increasing awareness, equal treatment and opportunities, having to think openly, having the same rights to learn.